# Simplify the expression -2(p + 4)^{2} - 3 + 5p. What is the simplified expression in standard form?

**Solution:**

The given expression is

-2(p + 4)^{2} - 3 + 5p

Using the algebraic identity (a + b)^{2} = a^{2} + b^{2} + 2ab

= - 2 (p^{2} + 16 + 8p) - 3 + 5p

By further simplification

= -2p^{2} - 32 - 16p - 3 + 5p

= -2p^{2} - 16p + 5p - 32 - 3

So we get

= -2p^{2} - 11p - 35

Therefore, the simplified expression in standard form is -2p^{2} - 11p - 35.

## Simplify the expression -2(p + 4)^{2} - 3 + 5p. What is the simplified expression in standard form?

**Summary:**

By simplifying -2(p + 4)^{2} - 3 + 5p, the expression in standard form is -2p^{2} - 11p - 35.